2022
DOI: 10.1002/anie.202212575
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Twisted Carbazole‐Fused DABNA Derivative as an Orange‐Red TADF Emitter for OLEDs with Nearly 40 % EQE

Abstract: Multiple resonance (MR) type thermally activated delayed fluorescence (TADF) material is currently a research hotspot in organic light‐emitting diodes (OLEDs) due to their high color purity and high exciton utilization. However, there are only a handful of MR‐TADF emitters with emissions beyond the blue‐to‐green region. The very limited emission colors for MR‐TADF emitters are mainly caused by the fact that so far molecular modifications of MR‐TADF do not offer much change in the emission colors. Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 73 publications
(8 reference statements)
0
32
0
Order By: Relevance
“…Its OLED achieved an EQE max of 39.2% at 588 nm and remained above 30.3% EQE even at high doping concentrations of 30 wt%. 130 In 2023, Yang et al proposed an effective method towards a long-wavelength MR-TADF emitter by integrating a strong electron-donating indolophenazine building block into the B/N-doped polycyclic aromatic hydrocarbons. The investigation of photophysical properties revealed that different electron-donating abilities had significant effects on luminescence features, including emission wavelength and FWHM.…”
Section: Boronmentioning
confidence: 99%
See 1 more Smart Citation
“…Its OLED achieved an EQE max of 39.2% at 588 nm and remained above 30.3% EQE even at high doping concentrations of 30 wt%. 130 In 2023, Yang et al proposed an effective method towards a long-wavelength MR-TADF emitter by integrating a strong electron-donating indolophenazine building block into the B/N-doped polycyclic aromatic hydrocarbons. The investigation of photophysical properties revealed that different electron-donating abilities had significant effects on luminescence features, including emission wavelength and FWHM.…”
Section: Boronmentioning
confidence: 99%
“…Its OLED achieved an EQE max of 39.2% at 588 nm and remained above 30.3% EQE even at high doping concentrations of 30 wt%. 130…”
Section: Highly Efficient Tadf Emitters Based On Three-coordinate Org...mentioning
confidence: 99%
“…[1][2][3][4][5] To date, TADF materials have been developed speedily, and the external quantum efficiency (EQE) of TADF devices have reached 40%. [6][7][8][9][10] However, these organic light-emitting diodes (OLEDs) devices with high EQE are mainly based on blue or green materials. In contrast, as one of the three primary colors indispensable in full-color displays, efficient red TADF-OLEDs still remain far behind.…”
Section: Introductionmentioning
confidence: 99%
“…Carbazole is a recurrent and highly versatile scaffold within chemistry, biomedicine, and materials science because of its attractive luminescent and semiconductor properties, which can be fine-tuned through not only the subtle and rational modification of its molecular structure but also imparting control over the interactions established with the environment at the supramolecular level. …”
Section: Introductionmentioning
confidence: 99%